Stabilization of Ni-YSZ Anodes in Solid Oxide Fuel Cells using an ALD-Grown Aluminum Titanate Interlayer - Zhuoming Feng; Katherine Hansen; Harish B. Bhandari; John M. Vohs (ECS Advances, 2024)
The effect of an Al _2 TiO _5 (ALT) interlayer between Ni and YSZ on enhancing the thermal stability of Ni-YSZ solid oxide fuel cell was examined. Atomic layer deposition (ALD) was used to provide precise control of the structure and thickness of the ALT interlayer. The study’s findings demonstrate that a 2 nm thick ALT interlayer deposited by ALD does not adversely affect the cell’s ohmic resistance and effectively prevents Ni sintering and the loss of active area during high-temperature heat treatments. ALT layers thicker than 2 nm, although they enhanced Ni stability, were found to impede oxygen ion transport in the electrode and significantly increase the ohmic resistance of the cell, leading to a decline in performance.